Problematic preventive efforts of sexual harassment through Islamic gender justice values-based education - Fadhilah, Ningsih; Rohmaniyah, Alfiatur (Universitas Islam Negeri Ar-Raniry, 2023)
This article aims to uncover preventive efforts against sexual harassment in higher education conducted by UIN KH Abdurrahman Wahid Pekalongan[1], which involved education based on Islamic gender justice. Education based on gender justice values in Islam needs to be carried out because Islam is a Rahmatanlil'alamin religion and is the main pillar of human values. This qualitative study employed interviews, observations, and documentation for collecting data. Meanwhile, the data analysis techniques proposed by Miles, Huberman, and Saldana, like data condensation, data presentation, concluding, and verification. The findings indicated that the portrait of sexual harassment phenomena among students could be considered an urgent condition. The student's understanding of sexual violence, Islamic gender justice, and preventing and handling sexual violence regulations was still inadequate. Moreover, various cases of sexual harassment, ranging from verbal to physical forms, have been identified. However, the preventive efforts against sexual harassment by UIN Gusdur through PSGA[2] and ULT SETARA[3] have been relatively effective. Meanwhile, education based on Islamic gender justice is carried out by socializing the problems cases regarding understanding gender and Islam.[1] K.H Abdurrahman Wahid Pekalongan State Islamic University (UIN) usually called UIN Gusdur Pekalongan, is located on Jl. Hero KM 5 Kajen Pekalongan Regency, Central Java 51156.[2] Center for Gender and Child Studies (PSGA) is a study center that focuses on issues of gender equality and justice in higher education [3] Integrated Service Unit (ULT) SETARA is a service under the center for gender and child studies which focuses on preventing and handling sexual violence at UIN Gusdur Pekalongan